Quality Markers of Dendrobium officinale by “Oligosaccharide-Spectrum-Effect” Relationships - Liu, Ruimin; Shi, Songshan; Xiong, Si; Su, Juan; Gan, Xiaona; Wu, Jianjun; Wang, Huijun; Wang, Shunchun (Frontiers in Nutrition, 2022)
Dendrobium officinale Kimura et Migo has been used as a traditional Chinese medicine and functional food for thousands of years. Carbohydrate is one of the most important effective substances and indicative components in D. officinale. However, due to the qualitative and quantitative analysis of polysaccharides in D. officinale remains challenge and limitation, herein, an oligosaccharide-quality marker approach was newly developed for quality assessment of D. officinale by spectrum-effect relationships between high performance liquid chromatographic (HPLC) fingerprints and anti-inflammatory effects. The HPLC fingerprints of 48 batches of oligosaccharides from D. officinale (DOOS) were developed and analyzed with similarity analysis and hierarchical cluster analysis, and eight common peaks were identified. In vitro screening experiment indicated that DOOS potentially inhibited NO production and effectively reduced the release of inflammatory cytokines such as TNF-α, IL-6, IL-1β in RAW 264.7 cells, thereby reducing the inflammatory response of cells. Finally, the HPLC fingerprint of different batches of DOOS combined with in vitro anti-inflammatory activity to assess the spectrum-effect relationships of DOOS by gray correlation analysis, in addition that the purified oligosaccharide components were identified and validated for NO inhibitory activity. Our results showed four DOOS (maltotetraose, maltopentaose, maltohexaose and mannohexaose) were relevant to anti-inflammatory effects, and could be as the quality markers for quality control of D. officinale. It suggests that the “oligosaccharide-spectrum-effect” relationships approach is a simple and reliable method for quality control of herb medicines or nutritious foods.